(3EMcGe GdCMcGe aj TQM CMGOjK SjO GdCfGes - (3ESeGYjd Hf CMeO Hf SYjO, YeGO GdOjf GHf JGL GdOjf GHf GdCKjQ , J (B699 (3g` s; (3GdLeGYjdj , Jbj GdOjf CHh eMeO,J (B600 (3g` s ((3eMeO Hf CHj Ydi s)
(3ChdgG (B:s
(3GdMeO ddg efhQ GdHUGFQ HMbGFb eYGQag , heUhQ GdNhGWQ NRGFf GdObGFb dWGFag s
(3BNQgG (B:s
(3BNQg ai HGH HjY GdeOHQceG ENJda GdYdeGA ai HjY GdeOHQ (B" (3ceG jbhd eGdc ai LhGR HjYg ai GdOjf Ydi GdJaUjd GdePchQ ai ePgHI , hePgH GdTGaYi ai LhGR HjYg eWdbkG hGddg CYde Je TQM YeOI GdCMcGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG SeGY ai SfI (B1114(3g` Ydi YR GdESdGe eMeO Hf UGdM GdYdbis
(3hSeGYGJ CNQi HYO Pdc heYGQVI HMGTjI JSei GdYOI s
(3hJedcGJ CbOegG SfI (B1136 (3g` s
(3hYdi GdfSNI JbjjOGJ s
Keywords: (3GdMOjK h GdeUWdMs